Effect of low-frequency low-intensity ultrasound with microbubbles on prostate cancer hypoxia - Rui Hou; Yanjun Xu; Qijie Lu; Yang Zhang; Bing Hu (Tumor Biology)
Angiogenesis plays an important role in tumor growth, invasiveness, and metastasis. It is well established that prostate cancer is exposed to fluctuating oxygen tensions and both acute and chronic hypoxia exist, and these conditions can upregulate angiogenesis-associated proteins such as hypoxia-inducible factor 1 alpha and vascular endothelial growth factor A. Low-frequency low-intensity ultrasound with microbubbles can induce obvious microvessel damage in tumors, cause cell necrosis or apoptosis. However, there is no information about whether the blocking blood effect of low-frequency low-intensity ultrasound with microbubbles has an influence on hypoxia environment of prostate cancer. Therefore, we investigated the impact of different low-frequency low-intensity ultrasound with microbubbles radiation times on prostate tumors, observed the change in the hypoxia-inducible factor 1 alpha and vascular endothelial growth factor A protein levels, as well as cell proliferation, apoptosis, and tumor volume. The results indicated that as the radiation was repeated four times on each treatment day, the effects of interruption were durable, the cell proliferation was inhibited, and apoptosis was promoted, and the hypoxia-inducible factor 1 alpha and vascular endothelial growth factor A expression levels were lower in the treatment group than in the control group. When the radiation was carried out once per treatment day, the hypoxia response was stimulated, the hypoxia-inducible factor 1 alpha and vascular endothelial growth factor A expression levels were higher compared with the control group, and cell proliferation was promoted. In addition, the tumor volume increased obviously in the hypoxia-stimulated group, whereas tumors grew slowly in the hypoxia-suppressed group. The results of this work demonstrated that under the same conditions, different radiation times of low-frequency low-intensity ultrasound with microbubbles affect the hypoxia response differently, and the effect at least partly stimulates or inhibits tumor growth.